2021
DOI: 10.3390/e23081080
|View full text |Cite
|
Sign up to set email alerts
|

Using the Relative Entropy of Linguistic Complexity to Assess L2 Language Proficiency Development

Abstract: This study applies relative entropy in naturalistic large-scale corpus to calculate the difference among L2 (second language) learners at different levels. We chose lemma, token, POS-trigram, conjunction to represent lexicon and grammar to detect the patterns of language proficiency development among different L2 groups using relative entropy. The results show that information distribution discrimination regarding lexical and grammatical differences continues to increase from L2 learners at a lower level to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Additionally, other information-theoretical metrics have been used to examine L2 complexity. Sun and Wang (2021) employed the relative entropy of linguistic complexity to examine the development of L2 learner proficiency. They concluded that relative entropy was a better measure of proficiency than traditional algorithms based on frequency summation or ratio.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, other information-theoretical metrics have been used to examine L2 complexity. Sun and Wang (2021) employed the relative entropy of linguistic complexity to examine the development of L2 learner proficiency. They concluded that relative entropy was a better measure of proficiency than traditional algorithms based on frequency summation or ratio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that relative entropy was a better measure of proficiency than traditional algorithms based on frequency summation or ratio. It should be noted, however, that Sun and Wang (2021) focused only on lexical and grammatical aspects, with minimal attention paid to morphological complexity. Paquot (2017) used the scores of Pointwise Mutual Information (PMI) to measure collocational complexity of phraseology, which is overlooked in previous L2 complexity research.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These unique characteristics might make Kolmogorov complexity a suitable measure to examine across and within L2 speaker variation in L2 writing. Despite their strengths, information-theoretic linguistic complexity measures have rarely been utilized in the L2 writing field [ 26 ], e.g., [ 50 , 63 ].…”
Section: Literature Reviewmentioning
confidence: 99%